Metagenomic sequencing revealed the potential of banknotes as a repository of microbial genes - Lin, Jun (BMC Genomics, 2021)
BACKGROUND: Genetic resources are important natural assets. Discovery of new enzyme gene sequences has been an ongoing effort in biotechnology industry. In the genomic age, genomes of microorganisms from various environments have been deciphered. Increasingly, it has become more and more difficult to find novel enzyme genes. In this work, we attempted to use the easily accessible banknotes to search for novel microbial gene sequences. RESULTS: We used high-throughput genomic sequencing technology to comprehensively characterize the diversity of microorganisms on the US dollars and Chinese Renminbis (RMBs). In addition to finding a vast diversity of microbes, we found a significant number of novel gene sequences, including an unreported superoxide dismutase (SOD) gene, whose catalytic activity was further verified by experiments. CONCLUSIONS: We demonstrated that banknotes could be a good and convenient genetic resource for finding economically valuable biologicals. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12864-021-07424-5.